Pengaruh globalisasi terhadap ketahanan pangan nasional - Sri Widodo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2003)
The problem on food security in Indonesia began to be interested since the economic crisis as one component of the social security net. Sustainable food security covers: availability of food, accessibility, utilization, stability, self reliance (autonomy) and sustainability. . Hirarchically food security can be at global order, regional, national, local, household and individual. The higher order offbod security is a necessary condition but not sufficient condition for the lower order.Economic theory indicate that there are gains to be made from free trade. increase the efficiency ufresource allocation, and increase welfare of all countries. However, all government, without exception, intervene to varying degrees in the working of natural market prces, with the reason the need to protect infant industry, to ensure food security, to redistribute income, and to enhance income of small producers.The liberalization initiatives culminated in UR agreement and WTO, among others, dismantling of quantitative restriction and subsidies as well as other nontariff barriers, but there were several new thing of antidumping tariff, sanitary and phytosanitary, technical barrier to trade,environment, and genetically modified organism.The impact of trade liberalization on exporter countries, in general, would benefit the producers, decrease the consumer surplus, and increase social welfare except large populated as India and China. The impact of importer countries depend on the policy of each country. Malaysia and Indonesia by decreasing import tariff policy would increase consumer surplus and social welfare but sacrificing the producers/farmers.National food policies consist of international trade policy domestic price policy, and policy on production efficiency. The international trade policy means to protect producers, consumers, and social welfare from the uncertainty of international market especially in the long run. The stabilization of domestic price policy needs inter department coordination and STE to implement. Protection could result inefficiency but it is needed for commodities those are not ready to compete and to protect from unfair trade, to protect farmers and long run food security.